2018
DOI: 10.1111/psyg.12338
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic comorbidities in patients with Alzheimer's disease and vascular dementia compared to a psychiatric control cohort

Abstract: Awareness of somatic comorbidities in patients with dementia is crucial to avoid complications during inpatient treatment. The occurrence of comorbid disorders was associated with longer and more frequent hospital stays, which potentially lead to higher health-care costs. Further studies should evaluate the causative association between somatic comorbidities and inpatient costs in dementia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…However, in this German study, the prevalence of hypertension, arrhythmias, and varicosis was less frequent in people with dementia than in the non‐dementia group. In our study, dementia diagnosis was identified by the use of medicines for dementia, which are restricted for people with Alzheimer’s disease, and this might contribute to the observed difference in the prevalence rates as some studies have suggested cardiovascular conditions are more common in people with vascular dementia than Alzheimer’s disease . In another study of 14,411 German people with Alzheimer’s disease, 7156 people with vascular dementia, and 34,534 comparison psychiatric patients without dementia, comorbidity of cardiac conditions (excluding hypertension) were more frequent in people with vascular dementia than in controls and Alzheimer’s patients .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, in this German study, the prevalence of hypertension, arrhythmias, and varicosis was less frequent in people with dementia than in the non‐dementia group. In our study, dementia diagnosis was identified by the use of medicines for dementia, which are restricted for people with Alzheimer’s disease, and this might contribute to the observed difference in the prevalence rates as some studies have suggested cardiovascular conditions are more common in people with vascular dementia than Alzheimer’s disease . In another study of 14,411 German people with Alzheimer’s disease, 7156 people with vascular dementia, and 34,534 comparison psychiatric patients without dementia, comorbidity of cardiac conditions (excluding hypertension) were more frequent in people with vascular dementia than in controls and Alzheimer’s patients .…”
Section: Discussionmentioning
confidence: 79%
“…It is unclear whether the lower prevalence of medicines used for cardiac conditions in people with Alzheimer's disease reflects appropriate treatment due to a lower prevalence of cardiovascular conditions in people with Alzheimer's disease or if it reflects a possible undertreatment of cardiovascular diseases. There were mixed reports regarding prevalence of comorbidity of cardiac conditions, with some studies reporting a higher prevalence, whereas others reported a lower prevalence of comorbidity of cardiac conditions in people with dementia than in the control group. A claims‐based study of 9139 German people with dementia and 28,614 comparisons without dementia found a significantly higher prevalence rate of cardiac insufficiency, stroke, diabetes, atherosclerosis/peripheral arterial occlusive disease, and mental and behavioral disorders in people with dementia than in those without dementia .…”
Section: Discussionmentioning
confidence: 98%
“…pneumonija bez febriliteta) i razvijati se vrlo brzo, neophodno je na vrijeme prepoznati problem (5). Potrebno je naglasiti da kod ovih bolesnika, čak i diskretna promjena u okruženju, a osobito dolazak na akutni odjel, može dodatno nepovoljno utjecati na psihičko i somatsko stanje bolesnika, uzrokovati komplikacije, intenzivno somatsko liječenje, dužu hospitalizaciju i veće troškove (1,2,6).…”
Section: Uvodunclassified
“…Due to the aging of the population, the proportion of the elderly in hospitals is increasing. The elderly population is also often associated with a greater number of chronic somatic diseases, especially for patients suffering from dementia (1,2). For dementia patients, the onset of somatic decompensation may lead to mental decompensation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation